Tuesday

October 21, 2014

October 21, 2014

Posted by **zohera** on Friday, September 21, 2012 at 12:50pm.

- math -
**Steve**, Friday, September 21, 2012 at 4:01pma^2b^(2/3) - (ab^2)^(2/3)

(a^2b)^(1/3) - (ab^2)^(1/3)(a^2b)^(1/3) + (ab^2)^(1/3)

ignoring the x's for a bit,

a^2 = (cot+tan)^2 = cot^2 + 2 + tan^2 = csc^2 + sec^2

a^2b = sec^3

b^2 = (sec-cos)^2 = sec^2 - 2 + cos^2

ab^2 = tan^3

(a2b)^(2/3) = sec^2

(ab^2)^(2/3) = tan^2

sec^2 - tan^2 = 1

**Answer this Question**

**Related Questions**

Pre-Calc - Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= ...

Math - Im really struggling with these proving identities problems can somebody ...

drwls - My previous question: Verify that (secx/sinx)*(cotx/cscx)=cscx is an ...

Math - Im really struggling with these proving identities problems can somebody ...

trig - prove cosx+cotx/secx+tanx =cosxcotx

college algebra - I think this is an exponential equation. I can not figure out ...

Precalculus/Trig - I can't seem to prove these trig identities and would really ...

precal - 1/tanx-secx+ 1/tanx+secx=-2tanx so this is what I did: =tanx+secx+tanx-...

Simplifying with Trigonometry Identities - Hi, I am a senior in High School ...

Math - 1)A piano tuner uses a tuning fork. If middle C has a frequency of 264 ...